Effects of different physical training protocols on ventricular oxidative stress parameters in infarction-induced rats - Pinho C.A.* (2012)
Aim: Physical exercise is important in the prevention and treatment of cardiovascular diseases. Nevertheless, controversy remains around type and intensity of effort required for significant biochemical protective changes. This study investigates two exercise protocols on ventricular oxidative parameters in rats post-infarction. Main methods: Thirty-six 2-month-old male Wistar rats were divided in two groups (n = 18): Sham and acute myocardial infarction (AMI) conducted by blocking the coronary artery. Thirty days after AMI, animals were divided in 6 subgroups (n = 6): sham, sham + continuous training (60 min), sham + interval training, AMI, AMI + continuous training, and AMI + interval training. Training was conducted in water (30-32 °C) 5 times a week for 6 weeks. Animals were sacrificed 48 h after the last exercise routine. Left ventricles were used for oxidative stress analyses (antioxidant enzyme activity and level, oxidative damage) and HIF1α and cit c oxidase expression. Key findings: After AMI, both exercise models decreased superoxide levels significantly. Training routines did not alter SOD expression and activity, though CAT expression increased with continuous training and GPX level diminished in both training groups, which coincided with the increase in GPX activity. Lipid damage decreased only in the continuous training group, while protein damage decreased only in the interval training group. Cytochrome C increased in both groups, while HIF-1 α dropped significantly after both exercise protocols. Significance: Significant improvement occurred in myocardium redox status in rats challenged with AMI after different training routines. However, continuous training seems to be more efficient in improving the parameters analyzed. © 2012 Elsevier Inc. All rights reserved.